Urban poverty in India - "Asthana, M. D. (ed.)" (New Delhi, 2004)
This book takes stock of the present poverty scenario in India. It is divided in sections headlined issues and policies, women as marginalised subset among the urban poor, Access to basic services, Shelter for the urban poor, and etc.
Keywords: Urban Poverty